2005
DOI: 10.1371/journal.pbio.0030326
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review—The Newcomers' Perspective

Abstract: The World Academy of Young Scientists argue that double blind peer-review will generate a better perception of fairness and equality in global scientific funding and publishing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…When more than 25% of department members attended this workshop, there was an increase in self-reported activity to promote gender equity at 3 months [47]. Furthermore, in contrast to the uncontrolled before-after study included in our review, anonymous review of applicants without disclosing the investigator’s name or gender was found to be effective in other settings [48], suggesting that it might be useful to test this strategy using a more rigorous design, such as in symphony orchestras and the technology industry [49–51]. Finally, when preparing peer review reports, peer reviewers may wish to ensure that they spend equal time on positive and negative aspects of the grant [52] and that they are aware of potential unconscious bias on gender differences [44].…”
Section: Discussionmentioning
confidence: 99%
“…When more than 25% of department members attended this workshop, there was an increase in self-reported activity to promote gender equity at 3 months [47]. Furthermore, in contrast to the uncontrolled before-after study included in our review, anonymous review of applicants without disclosing the investigator’s name or gender was found to be effective in other settings [48], suggesting that it might be useful to test this strategy using a more rigorous design, such as in symphony orchestras and the technology industry [49–51]. Finally, when preparing peer review reports, peer reviewers may wish to ensure that they spend equal time on positive and negative aspects of the grant [52] and that they are aware of potential unconscious bias on gender differences [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports based on reviewer surveys have shown that reviewers think that making themselves known to the author would discourage them from being critical or from reviewing altogether. 11,22,23 Despite blinding, reviewers can sometimes identify the author or at least the institution, 24 through the writing style, subject matter, opinions put forth, referenced articles or the practicalities of anonymising a submitted manuscript. The accuracy of guessed identities on blinded reviews in a variety of disciplines ranges between 25% and 42%.…”
Section: Blindingmentioning
confidence: 99%
“…The accuracy of guessed identities on blinded reviews in a variety of disciplines ranges between 25% and 42%. 24,25 Several authors have reported that blinding does not affect the quality of reviews, and that quality is more likely to be based on the word count than the blinding. [26][27][28] This has been attributed to the premise that those papers which would most benefit from blinding are the hardest to conceal as the authors would be well-known or reveal themselves through the references.…”
Section: Blindingmentioning
confidence: 99%
“…Two studies showed that editorial processes make articles more readable and improve the quality of reporting, but the findings may have limited generalizability to other journals. The authors concluded that editorial peer review, although widely used, is largely untested and its effects are uncertain 6 .…”
Section: Effects Of Editorial Peer Reviewmentioning
confidence: 99%